(untitled) (Journal of Hama University, 2019)
The aim of this research is to trace the circular path of a robotic vehicle using neural networks and to compare the performance of the network with the performance of follow the past algorithm. This research was confined to the circular track as the most applied path in the previous studies, which is difficult to trace for its warping, The deviation of the vehicle from the track for some reason during the change of speed specified, and to achieve the goal of the search was applied follow the past algorithm on the ring track and compare performance with the performance of the neural network. The algorithm gave good results for tracking the circular path, but when the speed of the robotic vehicle changed for some reason as an obstacle, it deviated considerably from its original trajectory. The use of neural networks as a technique to track the specific circular path has given good results compared to follow the past algorithm. The MATLAB program was used to model the vehicle and the path and to simulate the tracking of the specific circular path using the neural networks and follow the past algorithm.